Opsoclonus-myoclonus syndrome in the course of teratoma: a case report - Szczupak, Mateusz; Kobak, Jacek; Wiśniewska, Anna; Kosydar-Bochenek, Justyna; Jamro, Arkadiusz; Krupa-Nurcek, Sabina (Frontiers in Medicine, 2025)
Opsoclonus-myoclonus syndrome (OMS) is a rare neurological inflammatory disease of paraneoplastic, parainfectious or idiopathic origin. It is manifested by the occurrence of opsoclonus, myoclonus, ataxia, as well as behavioral and sleep disorders. The incidence is estimated at 1/5,000,000 people. This syndrome is usually immune-mediated and may be the first manifestation of cancer as a paraneoplastic syndrome, most often occurring in the course of breast, ovarian or lung cancer. Here we show a case of a 20-year-old woman with symptomatic opsoclonus-myoclonus syndrome in the course of teratoma. A brief review of the literature was conducted to determine the diagnostic route and treatment of this rare condition. As a result, it has been shown that the only method of treatment for OMS syndrome is the removal of the neoplastic lesion.